Love experienced by persons with disabilities - LIPIŃSKA-LOKŚ, JOLANTA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Jolanta Lipińska-Lokś, Love experienced by persons with disabilities. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 27-49. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.02 Humans as social beings feel natural attraction to being with other people, i.e. to establishing and maintaining relationships. Affiliations, such as friendship or love, significantly influence their development from the earliest years of life, either enriching or disturbing the quality of their functioning. Therefore, those who due to their health status or another life situation are marked by otherness, must be prepared to endure hardships. Consequently, persons with disabilities experience failures in their interpersonal contacts. They are often devoid of the opportunity to have a good friend or to experience true love, which may exacerbate their already difficult situation, often triggered within a family setting, where there was no acceptance and/or insufficient quality of parental love. All human beings, children in particular, need closeness and affection. Only then do they develop properly, experience happiness, see the meaning of their lives, feel loved and are able to reciprocate that love. Experiencing a disability or being a parent of a child with a disability may make love more difficult, perhaps even impossible. However, the desire for love can be so strong that it will manage to overcome all obstacles. Unfortunately, it may as well make life a grey existence filled with loneliness and suffering.